Psycho-pedagogical analys is of the formation of concepts learning and cognitive activity of students as the basis for the didactic intensification (retrospective review: XVII – beginning of XX century) (Pedagogy of Higher and Secondary Education, 2012)
Malykhina V. Psycho-pedagogical analys is of the formation of concepts learning and cognitive activity of students as the basis for the didactic intensification (retrospective review: XVII – beginning of XX century).The principal statements of the psychological-and-pedagogical analysis concerning the problem of uprising the conceptual theories investigating students’ learning and cognitive activities are illuminated in the article. The activities are regarded as the foundations for the didactic intensification (the results of some retrospective survey comprising the period from the birth time of Pedagogy in the ХVІІ th century and till the beginning of the XX th are represented).
Keywords: psychological-and-pedagogical analysis; students’ learning and cognitive activities; didactic intensification; retrospective survey